An outcomes evaluation of the ‘differentiated care’ antiretroviral therapy delivery in South African urban township - Tebeila, Tebogo (University of the Witwatersrand, Johannesburg, 2022)
With the high prevalence and massive expansion of antiretroviral therapy (ART), alternative ART delivery models are needed in scaling up, delivering ART, and maintaining high-quality services to people living with HIV. Various differentiated care ART delivery models were implemented in health facilities across South Africa, notable results from the literature suggest that differentiated care ART delivery models were piloted and implemented at scale, nevertheless, there is little evidence on the scale-up of these models on patients’ outcomes in South African urban townships. Ultimately, the research seeks to assess the outcomes of the differentiated care ART delivery models in a South African urban township called Tembisa in the Ekurhuleni Metropolitan Municipality. The research is a quantitative, retrospective cohort analysis. Logistic regression and Chi- square tests were used to determine rates of retention and factors associated with loss to follow-up. Behavioural theories were used to interpret the research findings. The research findings revealed that rates of retention were at 91.8 per cent and loss to follow-up was at 8.2 per cent. Furthermore, health facility, age at enrollment and duration on ART were associated with the probability of being lost to follow-up, nonetheless, there was no difference in sex and no association with modality. The finding from the study confirms that alternative ART care models are important in scaling up and delivering ART within an urban township setting, although there was poor viral load specimen collection at the scheduled clinic appointment good rates of retention in care and viral load suppression were achieved. Overall, the implementation of the intervention in a similar setting should be customized to patients aged between 18-24 years or younger, and those with a duration on ART of fewer than 24 months at enrollment differentiated care ART delivery models to reduce the probability of being lost to follow up after enrollment
A thesis presented in partial fulfillment for the degree of Master of Management (in the field of Public Sector Monitoring and Evaluation) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand February 2022
Keywords: HIV/AIDS; Differentiated care models; Antiretroviral therapy; Retention in care; Retention in care; UCTD; SDG-11: Sustainable cities and communities